Strategy of Cooperatives and Small and Medium Enterprises Service in Empowering Community Small and Medium Enterprises in Labuhan Batu Regency - Ricky Pane; Muhammad Arif (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
The role of SMEs in assisting local governments must be seen from: Their situation as the main players in financial training in various regions, the biggest job suppliers, important players in the progress of nearby businesses and strengthening local areas and development springs. The closest legislature in understanding a proper environment for MSMEs is not yet fully understood, it can be seen from the system and public strategy arrangements that the poor have agreed with MSMEs so that MSME actors are hampered within the monetary limits of item advertisements actually limiting environmental level decision making so that Regional. Governments do not yet have options. to provide capital and equipment assistance. - tools that can be used by entertainer MSME actors so that MSME actors look for their own capital and tools to wear the hijab. In addition, problems also come from MSMEs related to amateur administration, this is due to the limited information and talented human resources claimed by MSMEs so that public authorities who have the power and power in making strategies must help the private sector to provide preparations for MSMEs. to pass through. so that their business can fill up at a later date. The purpose behind this research is to find out the role of local government in involving small and medium enterprises (MSMEs) through the fostered service and SMEs in Labuhan Batu Regency. The examination used is an empirical juridical methodology. empirical juridical method is a strategy used to solve problems in research by looking at optional information and then proceeding to examine important information found in the field.